Answers

2015-12-03T17:40:31+05:30
Let α be 3 and β be -2.
sum=α+β=1
product=αβ=-6
Q.E=[x²-(sum)x+x]
      =[x²-1x+(-6)
      =x²-x-6
1 5 1
and i dnt hvae much pts to ask dis many questions
Question: 4x^2 - 16 + 15 = 0        4x^2/4 - 16x/4 + 15/4 = 0 ;    x^2 - 4x + 15/4 = 0;   x^2 - 2x(2) + (2)^2 - (2)^2 + 15/4 = 0;    (x-2)^2 - 4 + 15/4 = 0;    (x-2)^2 -(16+15)/4 = 0;    (x-2)^2 -1/4 = 0;     (x-2)^2 = 1/4;   (x-2) = +or- under root of 1/4,     (x-2) = +or- 1/2;   x= 2 + 1/2   or   x = 2 - 1/2
i do not know the last one now sorry
thank you u helped me 
u r really genuis